Icariin, a Novel Blocker of Sodium and Calcium Channels, Eliminates Early and Delayed Afterdepolarizations, As Well As Triggered Activity, in Rabbit Cardiomyocytes - Jiang, Wanzhen; Zeng, Mengliu; Cao, Zhenzhen; Liu, Zhipei; Hao, Jie; Zhang, Peipei; Tian, Youjia; Zhang, Peihua; Ma, Jihua (Frontiers in Physiology, 2017)
Icariin, a flavonoid monomer from Herba Epimedii, has confirmed pharmacological and biological effects. However, its effects on arrhythmias and cardiac electrophysiology remain unclear. Here we investigate the effects of icariin on ion currents and action potentials (APs) in the rabbit myocardium. Furthermore, the effects of icariin on aconitine-induced arrhythmias were assessed in whole rabbits. Ion currents and APs were recorded in voltage-clamp and current-clamp mode in rabbit left ventricular myocytes (LVMs) and left atrial myocytes (LAMs), respectively. Icariin significantly shortened action potential durations (APDs) at 50% and 90% repolarization (APD50 and APD90) and reduced AP amplitude (APA) and the maximum upstroke velocity (Vmax) of APs in LAMs and LVMs; however, icariin had no effect on resting membrane potential (RMP) in these cells. Icariin decreased the rate-dependence of the APD and completely abolished anemonia toxin II (ATX-II)-induced early afterdepolarizations (EADs). Moreover, icariin significantly suppressed delayed afterdepolarizations (DADs) and triggered activities (TAs) elicited by isoproterenol (ISO, 1 µM) and high extracellular calcium concentrations ([Ca2+]o, 3.6 mM) in LVMs. Icariin also decreased INaT in a concentration-dependent manner in LAMs and LVMs, with IC50 values of 12.28±0.29 µM (n=8 cells/4 rabbits) and 11.83±0.92 µM (n=10 cells/6 rabbits; p>0.05 versus LAMs), respectively, and reversed ATX-II-induced INaL in a concentration-dependent manner in LVMs. Furthermore, icariin attenuated ICaL in a dose-dependent manner in LVMs. The corresponding IC50 value was 4.78±0.89 µM (n=8 cells/4 rabbits), indicating that the aforementioned current in LVMs was 2.8-fold more sensitive to icariin than ICaL in LAMs (13.43±2.73 µM; n=9 cells/5 rabbits). Icariin induced leftward shifts in the steady-state inactivation curves of INaT and ICaL in LAMs and LVMs but did not have a significant effect on their activation processes. Moreover, icariin had no effects on IK1 and IKr in LVMs or Ito and IKur in LAMs. These results revealed for the first time that icariin is a multichannel blocker that affects INaT, INaL and ICaL in the myocardium and that the drug had significant inhibitory effects on aconitine-induced arrhythmias in whole rabbits. Therefore, icariin has potential as a class I and IV antiarrhythmic drug.